KOMUNIKASI TERAPEUTIK DAN KUALITAS PELAYANAN KESEHATAN: STUDI PADA PERAWAT RUMAH SAKIT UMUM SAWERIGADING KOTA PALOPO - Nurul Ilmi (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyse the role of nurses’ therapeutic communication in improving the quality of healthcare services at Sawerigading General Hospital, Palopo. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The informants included nurses, patients, patients’ families, and the hospital director. The findings reveal that therapeutic communication has been implemented according to established procedures through feedback techniques, empathy, and clear explanations, which help to build patient trust and support the healing process. Nevertheless, the effectiveness of therapeutic communication still encounters several barriers, namely internal factors of patients (physical condition, age, psychological aspects), external factors (noisy environment and room conditions), and socio-cultural factors (language differences and cultural background). These barriers often reduce the effectiveness of nurse–patient interactions and affect patient satisfaction. Therefore, it is essential to enhance nurses’ therapeutic communication skills through specialised training and to create a more conducive hospital environment. This study concludes that therapeutic communication is not merely a means of conveying information but also a strategic instrument in realising healthcare services that are humanistic, holistic, and patient-centred